TULBURĂRILE HEMOSTAZEI LA PACIENȚII CU NSTEMI ȘI MARKERII DE DIAGNOSTIC - DANILA Tatiana; MUNTEANU Mihaela; CIOBANU Lucia; POPOVICI Mihail; COBEȚ VALERIU (Academy of Sciences of Moldova, 2022)
Background. Hemostasis disorder is an important mechanism of cardiovascular disease, and its pathogenetic contribution to the evolution of NSTEMI is particularly notable in the context of the significance of the pathophysiological pattern caused by coronary microcirculation disorder. Highlighting imminent markers will facilitate the diagnosis and prognosis of NSTEMI. Object. Reporting literature summary data on markers with definite predictive value on proven hemostasis disorder in patients with NSTEMI. Results. The main markers of hemostasis disorder in NSTEMI and with predictive value on the diagnosis and evolution of post-infarction are:opposite the procoagulant system: elevation of microparticles derived from endotheliocytes and platelets expressing phosphotidylserine, activation of the complex of coagulation factors II, VII and X, formation of aggregates between platelets and leukocytes;opposite the anticoagulant system: increase in soluble thrombomodulin in combination with plasma decrease in antithrombin and C and S proteins;opposite the fibrinolytic system: elevation of the plasma levels of fibrin monomers and D-dimers of the plasminogen activator inhibitor in association with quantitative impairment of the plasminogen activator.